Os efeitos do estilo de liderança no comprometimento organizacional dos profissionais de tecnologia da informação - Muniz Filho, Sergio Mauro Salles (2013)
Because of the intensification of global competition, organizations need leaders that help to increase the commitment of the collaborators, since organizational commitment leads to improve productivity and competitiveness. Previous studies have shown a relationship between leadership and organizational commitment. The fast growth of information technology (IT) field combined with the dropout in IT courses has resulted in shortages of qualified professionals in the labor market. In this context, it turns increasingly important for organizations that their leaders influence the increasing of the organizational commitment of IT professionals because it is related not only to productivity, but also to a turnover reduction. The purpose of this study is to identify leadership styles that positively affect the organizational commitment of IT professionals. For this research, hypotheses tests were verified through survey research with IT professionals. The questionnaires were applied in order to identify the organizational commitment of the respondents and the leadership style used by their leaders. The survey results confirm the relationship between leadership style and organizational commitment, with emphasis on transformational leadership that has shown to be positively related to affective commitment and instrumental commitment of IT professionals.